2011
DOI: 10.1007/s11249-011-9885-4
|View full text |Cite
|
Sign up to set email alerts
|

Ni3Al Matrix Composite with Lubricious Tungstate at High Temperatures

Abstract: Ni 3 Al-Ag-BaF 2 /CaF 2 -W composites were fabricated by the powder metallurgy route, and their tribological properties over a wide temperature range, starting from room temperature up to 800°C, were investigated. The Ni 3 Al matrix composite with 15 wt% BaF 2 /CaF 2 exhibited a favorable friction coefficient (range 0.3-0.4) and wear rate (0.2-6.2 9 10 -4 mm 3 N -1 m -1 ). The formation of BaWO 4 and CaWO 4 with lubricity on the worn surface due to a tribo-chemical reaction at high temperatures provided excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…As expected, barium and calcium tungstates with lubricious properties contributed to low friction coefficient at elevated temperatures [50].…”
Section: Effect Of Reinforcement On the Tribological Behaviorsupporting
confidence: 77%
See 1 more Smart Citation
“…As expected, barium and calcium tungstates with lubricious properties contributed to low friction coefficient at elevated temperatures [50].…”
Section: Effect Of Reinforcement On the Tribological Behaviorsupporting
confidence: 77%
“…Recently, a series of Ni3Al high temperature self-lubricating composites were developed in Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences [15,[48][49][50][51][52][53][54][55]. The selflubricating composites, which consist of Ni3Al matrix with Cr/Mo/W, Ag and BaF2/CaF2 additions, exhibit the low friction coefficient and wear rate at a wide temperature range from room temperature to 1000 °C.…”
Section: Ni3al Matrix High Temperature Self-lubricating Compositesmentioning
confidence: 99%
“…Traditional lubricating oils and greases could not withstand temperatures exceeding 300 C. Therefore, lubrication at this temperature is normally focused on metal matrix, 1,2 intermetallic matrix 3,4 and ceramic matrix 5 lubrication coatings. However, these solid lubrication coatings need to be pre-coated to the friction surface before friction can commence.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al 8,9 reported the friction and wear performances of TiAl matrix self-lubricating composites reinforced by different solid lubricants at high temperatures and also observed that the solid lubricant lms formed on the worn surfaces improved the friction and wear performances of the composites. Zhu et al 10,11 explored the tribological performances of Ni 3 Al matrix self-lubricating composites reinforced by Ag and BaF 2 /CaF 2 at elevated temperatures and noticed that the tribological performances were enhanced over pure Ni 3 Al alloy, which was attributed to the formation of solid lubricant lms on the worn surfaces. Xu et al 12 investigated the tribological properties of TiAl matrix self-lubricating composites reinforced by WS 2 and ZnO and found that solid lubricant lms were formed on the worn surfaces, which were benecial for the improvement of tribological properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [10,11] explored the elevated temperature tribological performances of Ni 3 Al matrix self-lubricating composites reinforced by Ag and BaF 2 /CaF 2 and noticed that the tribological performances were enhanced over pure Ni 3 Al alloy, which was attributed to the formation of solid lubricant films on the worn surfaces. Xu et al [12] investigated the tribological properties of TiAl matrix self-lubricating composites reinforced by WS 2 and ZnO and found that the solid lubricant films formed on the worn surfaces, which were benefited to the improvement of tribological properties of composites.…”
mentioning
confidence: 99%